Serum Amyloid Beta Precursor Protein, Neurofilament Light, and Visinin-like Protein-1 in Rugby Players: An Exploratory Study - Jessica E. Morgan; Sarean A. Gaynor-Metzinger; Steven D. Beck; Iustin C. Scobercea; India J. Austin; Hannah E. Blankenship; Julien S. Baker; Allan Knox; Jorge M. Serrador; Matthew J. Rogatzki (Sports, 2022)
Concussion diagnosis is difficult and may be improved with the addition of a blood-based biomarker that indicates concussion. The purpose of this research was to investigate the capability of serum amyloid beta precursor protein (APP), neurofilament light (NfL), and visinin-like protein-1 (VILIP-1) to distinguish athletes who were diagnosed with a concussion pitch-side. An observational cross-sectional study design was used to replicate sideline concussion diagnosis. Subjects included mutually exclusive pre-match (n = 9), post-match (n = 15), and SRC (n = 7) groups. Six paired pre-and post-match subjects were analyzed for APP. APP increased significantly from pre-match (mean = 57.98 pg·mL−1, SD = 63.21 pg·mL−1) to post-match (mean = 111.37 pg·mL−1, SD = 106.89 pg·mL−1, p = 0.048) in the paired subjects. NfL was lower in the SRC group (median = 8.71 pg·mL−1, IQR = 6.09 pg·mL−1) compared to the post-match group (median = 29.60 pg·mL−1, IQR = 57.45 pg·mL−1, p < 0.001). VILIP-1 was higher in the post-match group (median = 212.18 pg·mL−1, IQR = 345.00 pg·mL−1) compared to both the pre-match (median = 32.63 pg·mL−1, IQR = 52.24 pg·mL−1), p = 0.001) and SRC (median = 30.21 pg·mL−1, IQR = 47.20 pg·mL−1), p = 0.003) groups. APP, NfL, and VILIP-1 were all able to distinguish between pre-match and post-match groups (AUROC > 0.700) but not from the SRC group (AUROC < 0.660). Our results show that APP, NfL, and VILIP-1 were not helpful in differentiating concussed from non-concussed athletes pitch-side in this study.